Multi Response Optimization of Turning Process by Considering its Cutting Parameters Implementing Grey Relational Analysis - Pathapalli, Venkateshwar Reddy; P, Srinivasa Rao; Basam, Veerabhadra Reddy; Doni, Mohana Krishnudu (International Journal of Integrated Engineering, 2019)
Machining process is most broadly utilized in the manufacturing industries. The purpose of the present effort is to investigate the cutting parameters in turning process on the responses: â€˜Material Removal Rateâ€™, â€˜Surface Roughnessâ€™ and â€˜Tool Wear Rateâ€™ in CNC turning of EN8 steel using tool made of tungsten carbide. Three factors namely â€˜Cutting Speedâ€™, â€˜feed rateâ€™ and â€˜depth of cutâ€™ with each of the three levels have been considered as the cutting parameters. In the present study using the Taguchi’s DOE methodology, multi-response optimization is carried out using Grey Relational approach to optimize the responses. Taguchiâ€™s L9 orthogonal array is used to conduct the experiments. The obtained results are then analyzed by the Grey Taguchi. Grey Taguchi Method is implemented to find the optimal levels for the parameters. Validation test is performed to confirm the optimal levels.